Transmembrane adaptor protein WBP1L regulates CXCR4 signalling and murine haematopoiesis - Borna, Simon; Drobek, Ales; Kralova, Jarmila; Glatzova, Daniela; Splichalova, Iva; Fabisik, Matej; Pokorna, Jana; Skopcova, Tereza; Angelisova, Pavla; Kanderova, Veronika; Starkova, Julia; Stanek, Petr; et al. (Journal of cellular and molecular medicine, 2020)
WW domain binding protein 1-like (WBP1L), also known as outcome predictor of acute leukaemia 1 (OPAL1), is a transmembrane adaptor protein, expression of which correlates with ETV6-RUNX1 (t(12;21)(p13;q22)) translocation and favourable prognosis in childhood leukaemia. It has a broad expression pattern in haematopoietic and in non-haematopoietic cells. However, its physiological function has been unknown. Here, we show that WBP1L negatively regulates signalling through a critical chemokine receptor CXCR4 in multiple leucocyte subsets and cell lines. We also show that WBP1L interacts with NEDD4-family ubiquitin ligases and regulates CXCR4 ubiquitination and expression. Moreover, analysis of Wbp1l-deficient mice revealed alterations in B cell development and enhanced efficiency of bone marrow cell transplantation. Collectively, our data show that WBP1L is a novel regulator of CXCR4 signalling and haematopoiesis.
Keywords: CXCR4; lipoylace; Glycoproteins; Germ Cells; membránové proteiny; signální transdukce; Receptors, CXCR4; Membrane Proteins; Protein Binding; HEK293 Cells; receptory CXCR4; hematopoéza; adaptorové proteiny signální transdukční; myši inbrední C57BL; ubikvitinace; Signal Transduction; ubikvitinligasy; Lipoylation; Ubiquitination; haematopoietic stem cell; bone marrow homing; Ubiquitin-Protein Ligases; haematopoiesis; zvířata; HEK293 buňky; Adaptor Proteins, Signal Transducing; Humans; RUNX1; homeostáza; OPAL1; vazba proteinů; zárodečné buňky; bone marrow transplantation; malá interferující RNA; hematopoetické kmenové buňky; Hematopoiesis; glykoproteiny; Homeostasis; ETV6; WBP1L; Hematopoietic Stem Cells; RNA, Small Interfering; Mice, Inbred C57BL; lidé; NEDD4 family; Animals